ANALYSIS OF THE BEHAVIOR OF STAI SANGATTA STUDENTS IN ONLINE SHOPPING - Alda Sevia Tamara; Adelia Septiani Putri; Dhea Rahmadanie; Geby Aprilia Asawib (Antis Publisher, 2024)
General Background: The rapid development of information technology has revolutionized consumer behavior, particularly among university students, who are increasingly turning to online shopping as a preferred mode of consumption. Specific Background: This trend is evident among students of STAI Sangatta, where online platforms such as Shopee, Tokopedia, and Lazada dominate shopping habits. Despite its growing popularity, the phenomenon of online shopping remains underexplored, especially concerning its implications on behavior and decision-making processes among students. Knowledge Gap: Limited research exists that examines the motivations, preferences, and challenges faced by students in this context, particularly in terms of potential ethical and behavioral concerns. Aims: This study aims to analyze the online shopping behavior of STAI Sangatta students, focusing on their motivations, experiences, and the implications of their consumption patterns. Results: Findings indicate that online shopping is driven by convenience, access to quality information, and a desire to maintain self-image and lifestyle. Students often purchase skincare and fashion items, frequently leading to excessive and consumptive behavior. Key challenges identified include mismatched product expectations, long delivery times, and high shipping costs. Additionally, ethical concerns such as potential elements of usury, gharar (fraud), and harm to others’ rights emerged as critical issues affecting satisfaction and decision-making. Novelty: The study highlights the dual motivations of necessity and lifestyle among students, offering new insights into the ethical dimensions of online shopping behaviors in a specific cultural and religious context. Implications: The findings emphasize the need for awareness campaigns and educational interventions to promote responsible online shopping behaviors among students while addressing ethical concerns in e-commerce practices.